The Effect of Adding Expanded Polystyrene Beads (EPS) on the Hardened Properties of Concrete - Salahaldeen, A. S.; Al-Hadithi, A. I. (Engineering, Technology & Applied Science Research, 2022)
This study investigated the possibility of producing lightweight concrete using Expanded Polystyrene Beads (EPS), using one reference and five light concrete mixes by replacing coarse aggregates with EPS grains in five volumetric ratios: 20, 40, 60, 80, and 100%. The properties of hardened concrete of all mixed specimens, such as compressive strength, flexural strength, and density, were evaluated. The results showed that the addition of EPS caused an apparent reduction in the mechanical properties of concrete. The compressive strength at 28 days of curing ranged from 13.6 to 1.96MPa, while the rupture modulus ranged from 2.26 to 0MPa. Adding EPS grains as coarse aggregates led to a decrease in the concrete’s weight. Replacing the coarse aggregates with EPS grains resulted in lightweight concrete with a density of 1086.5kg/m3.